Effectiveness of ICT Based Learning Material in Science Learning - Altaf, Faiza; Abraham, Jessy (Indian Journal of Educational Technology, 2021)
In the present study researchers developed an /CT based learning material. It was a self/ earning material, which was based on the principles of programmed learning. In the present study, an /CT based programmed learning material was developed on the topics "Matter in our surroundings" and "Is matter around us pure" based on the content of the NCERT Science textbook for class IX Students. The sample for the present study comprised of 180 students of class IX. A quasi-experimental research design was adopted for the study. This study involved the dependent variable as -Treatment Groups (Experimental Group Vs. Control Group} and an independent variable as- Achievement scores of students. An /CT based Programmed Learning Material, Pre, and Post achievement tests developed by the researchers were used. The data were analyzed by using the Mean, S. D., and Analysis of variance. Analysis of data revealed that teaching with an /CT based programmed learning material is more effective for the students as compared to the conventional method of teaching.